Fonctions des barrages de correction torrentielle - Guillaume Piton (Unité Mixte de Recherche 8504 Géographie-cités, 2019)
For over 150 years, humans have tried to limit the geomorphic activity of mountain watercourses, and the related damage, using torrent control works. Check dams are likely the most emblematic civil engineering structures used in mountain system soil conservation programs. Modern mountain societies have inherited thousands of these structures built in upland gullies and streams. The expected qualitative effect of check dams on river systems is referred to their function. Check dam function must be clearly understood to help define their effectiveness and decisions concerning their maintenance or new project designs. The next steps concern quantitative assessments of each function on the flood features and propagation of all effects through the sediment cascade. The present understanding of these sometimes old structures’ functions can be complicated because the societal and environmental contexts in which the original structures were built may have changed. To bridge this gap, this paper traces the purposes for which check dams were built, through a detailed analysis of French archives. We first analyze chronologically how each function was theorized and applied in the field. In the nineteenth century, engineers developed a thorough empirical and conceptual knowledge of mountain soil erosion, torrential geomorphology, and sediment transport processes as well as check dam interactions with these natural processes. The second part of this paper synthesizes conceptual descriptions of the check dams’ functions, in the light of more than 150 years of experience. The French experience is compared to other countries’ pioneering works. Finally, the next steps and remaining research challenges toward a comprehensive analysis of check dams’ efficiency in torrent hazard mitigation are presented. This analysis is proposed to remind how, conceptually, check dams may influence geomorphic systems, bearing in mind the knowledge represented in pioneer guidelines and recent works on the subject.